A comparative analysis of sampling methodologies for assessing abundance and distribution of young-of-the-year groundfishes in nearshore soft-sediment habitats - Lockhart, Katlyn; Ciannelli, Lorenzo; Wakefield, W. Waldo (Fisheries research, 2023)
Groundfishes are important species for commercial, recreational, and tribal fisheries along the Pacific Coast of the United States. Understanding the abundance and distribution of these fishes is necessary for successful fisheries management. Many groundfish species spend at least part of their life cycle in nearshore habitats. However, assessing groundfish species assemblages in nearshore habitats can be limited by the relatively small size of young-of-the-year and subadult life history stages, which may not be quantitatively retained with traditional survey gears. In addition, portions of the innermost nearshore (<55 m water depth) can be inaccessible to vessels employed in trawl surveys. To help improve the fishery-independent data informing the current understanding of nearshore assemblages, we compared catches resulting from two different but spatially overlapping surveys. One is the National Oceanic and Atmospheric Administration’s (NOAA) West Coast Groundfish Bottom Trawl Survey (WCGBTS), which is representative of a typical groundfish survey in USA and EU continental shelf habitats. The other is an ad-hoc beam trawl survey along the Newport Hydrographic (NH) Line – an oceanographically well-monitored sampling line off the Pacific Coast. Our objectives were to evaluate the representativeness of nearshore fish communities in the WCGBTS and to assess if additional nearshore sampling would enhance the WCGBTS. For the purposes of this study, “nearshore” is defined as the continental shelf shoreward of 200 m depth. Examining fish catches and environmental variables from both surveys, we found significant differences in fish assemblages, oxygen, temperature, and salinity based on depth, season, year, and survey type. The WCGBTS is designed and well-suited for sampling subadult and adult groundfishes in trawlable habitat. However, year-round sampling of the beam trawl survey allows it to capture ephemeral environmental conditions better than the WCGBTS. The gear type and sampling location make the beam trawl survey better suited than the WCGBTS for sampling smaller individuals and species that live at shallower depths. The beam trawl survey caught 69 unique species or taxa groups within the comparative data subset, whereas the WCGBTS caught 83. The three most commonly occurring species in the beam trawl survey were Pacific sanddab (Citharichthys sordidus), English sole (Parophrys vetulus), and speckled sanddab (Citharichthys stigmaeus), while the WCGBTS most commonly caught rex sole (Glyptocephalus zachirus), Dover sole (Microstomus pacificus), and spotted ratfish (Hydrolagus colliei). Of the fish with measured lengths, the catch from the beam trawl survey had a mode standard length of 2 cm, contrasted with the mode length (total length, fork length, anal length, and natural length combined) of 22 cm for the WCGBTS. We found that there is a transition in species assemblages right where the WCGBTS ends (about 55 m). Thus, while the surveys overlap in some capabilities, this analysis shows that the beam trawl survey or a similar nearshore survey would complement the WCGBTS, providing an enhanced characterization of groundfish assemblages. •Juvenile groundfish assemblages may not be well sampled in stock assessment surveys.•Compared inner continental shelf fish assemblages: beam trawl vs. Aberdeen trawl.•There is a transition in species composition where stock assessment survey ends.•Beam trawl survey better represents young-of-the-year flatfish assemblages.•Beam trawl survey provides improved seasonal and shallow depth (< 55 m) coverage.